Right versus left thoracic approach esophagectomy for patients with neoadjuvant immunochemotherapy - Kexi Wang; Xuan Xie; Jianqun He; Shuogui Fang; Yiming Zhong; Duoguang Wu; Kefeng Wang; Minghui Wang (Annals of Medicine)
Background The purpose of this study was to investigate the safety and efficacy of left thoracic approach (LTA) and right thoracic approach (RTA) in patients with esophageal squamous cell carcinoma (ESCC) after neoadjuvant immunochemotherapy (NICT).Methods This study included 83 ESCC patients who underwent right transthoracic esophagectomy (n = 61) and left transthoracic esophagectomy (n = 22) after NICT in our hospital from October 2019 to September 2023. The data of these patients were retrospectively analyzed.Results Compared with the LTA group, the RTA group had a longer operation time (245.6 ± 27.8 min vs. 356.5 ± 83.2 min, p < 0.001) and more lymph nodes were removed (21.0 ± 7.9 vs. 29.3 ± 10.8, p = 0.001). The 3-year disease free survival (DFS) of the LTA group and the RTA group were 61.0% and 65.7% (p = 0.861), and the 3-year overall survival (OS) were 60.7% and 77.4% (p = 0.753) respectively. There was no significant difference in prognosis between the two groups. Lymphovascular invasion was an independent risk factor for DFS (HR = 4.042, p = 0.004) and OS (HR = 4.607, p = 0.003) in patients with ESCC undergoing NICT combined with surgery.Conclusion There was no difference in postoperative complications and short-term survival in patients with ESCC underwent surgery after NICT regardless of left or right thoracic approach. It is worth noting that lymphovascular invasion has an important impact on the prognosis of these patients.